2023
DOI: 10.29100/jipi.v8i1.3278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kesuksesan Implementasi Sap Di Masa Pandemi Covid-19 Menggunakan Model Utaut 3 Pada Pt. Kai

Abstract: Proses bisnis PT KAI didukung oleh integrasi sistem SAP sejak tahun 2012 hingga keadaan pandemi saat ini, ditemukan beberapa permasalahan dalam implementasi yaitu terjadinya penurunan nilai kinerja karyawan pengguna SAP pada PT KAI selama penerapan metode kerja hybrid yang merupakan imbas dari pandemi COVID-19. Berdasarkan dari permasalahan tersebut penelitian ini berfokus pada analisa kesuksesan implementasi SAP yang dilihat dari sikap pengguna dalam menerima implementasi SAP dimasa pandemi COVID-19 melalui m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Factors in the work environment, such as organizational policies, work culture, and supervisor support, can influence individuals' perceptions of their behavioral control regarding the use of SAP software. If the work environment supports the use of the software and provides incentives or encouragement to use it, this will strengthen the individual's positive intentions to adopt it (Layongan et al, 2022;Zulaikah et al, 2023). Previous experience using similar technology or software may also influence perceived behavioral control.…”
Section: Discussionmentioning
confidence: 99%
“…Factors in the work environment, such as organizational policies, work culture, and supervisor support, can influence individuals' perceptions of their behavioral control regarding the use of SAP software. If the work environment supports the use of the software and provides incentives or encouragement to use it, this will strengthen the individual's positive intentions to adopt it (Layongan et al, 2022;Zulaikah et al, 2023). Previous experience using similar technology or software may also influence perceived behavioral control.…”
Section: Discussionmentioning
confidence: 99%
“…Building upon the studies conducted by Venkatesh et al, (2012), Farooq et al, (2017), and Zulaikah et al, (2023), price value has been shown to influence behavioral intention. In this study, price value refers to the tradeoff between the benefits received from using the mobile banking application and the cost incurred for the transactions.…”
Section: The Effect Price Value On Behavioral Intentionmentioning
confidence: 98%